Sufi Narratives of Intimacy: Ibn Arabi, Gender, and Sexuality By Sa’diyya Shaikh (Chapel Hill: University of North Carolina Press, 2012. 304 pages.) (American Journal of Islam and Society, 2014)
Sa’diyya Shaikh’s groundbreaking Sufi Narratives of Intimacy: Ibn Arabi,Gender, and Sexuality not only makes a significant contribution to the growingbody of scholarship on issues of gender and Islam, but also serves as an eloquentand accessible introduction to the life and work of Muhyi al-Din ibnArabi, unquestionably one of the most important voices in the Islamic tradition.Moreover, it is a rigorous piece of academic scholarship rooted in a thoroughknowledge of Islam’s primary sources and a sophisticated understandingof contemporary methodology, both in the academic study of religion andwomen and gender studies. At the same time, it adds significantly to normativediscussions within Islam – the crucial debates about gender and sexuality, theongoing arguments on the nature of authority in Islam, and the role of fiqh,kalām, and Sufism within the Muslim tradition. It succeeds brilliantly as ascholarly examination of Ibn Arabi’s work and as an example of feministscholarship at its very best.For me, the most important aspect is how the book functions as an introductionto the thought of Ibn Arabi, a notoriously demanding thinker whosework can sometimes appear impenetrable. As a result, much of the previousscholarship on him, including the essential and pioneering work of William ...